The Comparasion Determining of Some Route of Angkot In Bandung by Using Greedy Algorithm and Min Plus Algorithm - Susilowati, Eka (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2018)
Bandung is one of the major cities in Indonesia. The lower middle class is greatly helped by public transportation. Angkot is transportation that is close to the people. However, public transportation services that are less organized can make people switch to using private transportation. This actually has a bad impact on traffic. Thus, there need to be improvements in public transportation in the city of Bandung. One-way roads in the city of Bandung are also the cause of many angkot routes. The choice of public transportation users to choose an efficient angkot route. Efficient here means a short path so that the travel time to the destination is minimal. In the previous article, the Cicaheum Ciroyom and Ujung Berung ITB angkot routes were obtained using the Greedy algorithm. In this discussion, the algorithm that can be used to determine angkot routes in Bandung is the Min-Plus algorithm. After being compared between the Greedy algorithm and the Min plus algorithm, the resulting angkot algorithm is better obtained by the Min Plus algorithm.